2016
DOI: 10.1088/0953-8984/28/39/395201
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the electronic specific heat on swift heavy ion irradiation simulations of silicon

Abstract: Abstract. Swift heavy ion (SHI) irradiation of materials is often modelled using the two-temperature model. While the model has been successful in describing SHI damage in metals, it fails to account for the presence of a bandgap in semiconductors and insulators. Here we explore the potential to overcome this limitation by explicitly incorporating the influence of the bandgap in the parameterisation of the electronic specific heat for Si. The specific heat as a function of electronic temperature is calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The thermal conductivity of the lattice is chosen to be λ l = 130 W/mK for simplicity in this calculation. The specific heat of the electron depends on the electron temperature, and we use a linear relation C e = γ T e , where γ = 50 J/m 3 K 2 [41]. We assume electron thermal conductivity in silicon follows the Wiedemann-Franz law, λ e = Lσ T e , where Lσ = 24.4 µW/mK 2 [42].…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal conductivity of the lattice is chosen to be λ l = 130 W/mK for simplicity in this calculation. The specific heat of the electron depends on the electron temperature, and we use a linear relation C e = γ T e , where γ = 50 J/m 3 K 2 [41]. We assume electron thermal conductivity in silicon follows the Wiedemann-Franz law, λ e = Lσ T e , where Lσ = 24.4 µW/mK 2 [42].…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…We assume electron thermal conductivity in silicon follows the Wiedemann-Franz law, λ e = Lσ T e , where Lσ = 24.4 µW/mK 2 [42]. Following the methodology in Khara et al, the lattice-electron coupling term is calculated to be G = 2.8 × 10 17 W/m 3 K [41]. The solid-liquid coupling coefficient is chosen W = 10 8 W/m 2 K as the description following Equation (9).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Silicon is a widely studied material in the context of strongly driven phase transitions, both experimentally [1][2][3][4][5][6] and theoretically [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], where it is found to melt on a subpicosecond timescale at high excitations. Most theoretical studies of nonthermal melting in silicon have employed ab initio simulation methods.…”
Section: Introductionmentioning
confidence: 99%
“…In these materials is zero at low because there is insufficient thermal energy to excite electrons across the gap. As is very sensitive to the size of the bandgap, it is necessary to employ a DFT functional that correctly reproduces this feature, as it has been demonstrated that different functionals produce very different degrees of damage in SHI simulations of silicon [37]. Calculating the dependence of for band gap materials is more challenging as ( )is zero in these materials so equation 3.1 diverges.…”
Section: Figure 2: a Schematic Representation Of The Energy Depositiomentioning
confidence: 99%
“…The model was coupled to MD to give an extended version of 2T-MD and used to model SHI irradiation in Ge [68]. As argued above, however, the use of the electron density as an additional parameter is unnecessary, and other studies of SHI irradiation in Si [37], UO2 [69] and SiO2 [70] have omitted it.…”
Section: Shi Irradiationmentioning
confidence: 99%